DSP implementation of fuzzy controlled magnetic levitation system - Orhan, Ahmet; Akin, Erhan; Karakose, Mehmet (Springer-Verlag Berlin, 2001)
This paper presents a fuzzy logic based controller applied to a magnetic levitation (MAGLEV) system. MAGLEV system is nonlinear and complex. It is difficult to obtain exact mathematical model. To improve control performance, an inner current control loop has been used. The proposed controllers for MAGLEV system is simulated by using MATLAB-SIMULINK and implemented on an experimental system using a TMS320C31 digital signal processor.
7th Fuzzy International Conference on Computational Intelligence -- OCT 01-03, 2001 -- Dortmund, GERMANY